Penerapan Algoritma Boruvka Pada Jaringan Listrik : (Studi Kasus Pada Kelurahan Tanjung Pinggir Kecamatan Siantar Martoba) - Novita Sari Saragih; Mulyono Mulyono (Lembaga Pengembangan Kinerja Dosen, 2023)
This research was conducted in Tanjung Pinggir, Siantar Martoba District to determine the optimization of electrical installations using the Boruvka algorithm to find a minimum spanning tree node with a minimum number of 3 consecutive nodes. Edges that do not form a circuit. Based on data obtained from PT. PLN (Persero) UP3 Pematangsiantar, then a picture of the installed network graph is obtained. The results obtained for the electrical installation diagram were obtained by using Python and the 2,591 meter Boruvka algorithm to obtain a minimum spanning tree. In this case, the electricity distribution cable is reduced by 41 meters compared to the previous total installation of 2,632 meters.